Peritoneal fluid stimulates neoplastic transformation of normal HEK 293 cells by high expression of pluripotent genes - Szabłowska-Gadomska, Ilona; Ducher, Magdalena; Orzechowska, Magdalena; Bogusławska-Duch, Joanna; Kowalska, Magdalena; Poławska, Helena; Małecki, Maciej (Polish Journal of Pathology, 2018)
Gynecological cancers constitute a serious problem in the world. Their advanced stages are often characterized by the accumulation of ascites, which leads to spreading of cancer cells outside their primary focus. Despite progress in the treatment, prognoses are still not satisfactory. The main causes of these failures are chemoresistance, metastases and recurrences of the disease, which is influenced by, among others, the microenvironment of cancer cells. This study investigated the effect of the microenvironment, which create ascites derived from patients with ovarian and endometrial cancer to non-gynecological HEK 293 cells. The effect of the gynecological cancer microenvironment on HEK 293 cells behaviour was analysed using RT-PCR, qRT-PCR, Western blotting and functional analysis (invasion assays, hanging drop) methods. Our results suggest that the key genes for the development of cancer can be regulated by epigenetic and hypoxia-inducible factor in dependent manner. It was observed that in vitro microenvironment, which is created by cells originating from patients with gynecological cancer (ovarian cancer, endometrial cancer) is able to generate changes in HEK 293 cells by itself.